Properties Of Suweg (Amorphophallus Campanulatus B1) And Its Glicemic Index - Didah Nur Faridah (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2005)
Suweg (Amorphophallus campanulatus B1) is an indigenous tuber potentially used as an alternative food source. The objective of the study was to identify the functional properties, i.e. dietary fiber and Glicemic Index (IG) of Suweg by in vivo method using human. The experiment was conducted in three steps i.e suweg flour production, analysis of suweg flour functional properties, and determination of glycemic index (IG) using human. Suweg tuber had high content of dietary fiber (13,71%), and protein (7,20%) but had low fat content (0,28%). Suweg tuber had low IG (42) with low starch in vitro digestibility (61,75%), hence its was categorized as food product with low IG (